2017
DOI: 10.1016/j.orcp.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between peer teasing in childhood and young men’s obesity

Abstract: Objective Being teased and otherwise victimized by peers during childhood increases risk for obesity. However, few prospective studies have considered whether risk extends to adulthood. We tested whether being teased in childhood predicted higher body mass index (BMI) and increased odds of obesity in early adulthood in a community sample of American males. Method Boys (n = 206) were classified as victims of peer teasing or non-victims (n = 55 and 151, respectively) based on mother, father, and teacher report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Thus, apart from poor parenting or concurrent socioemotional risks, children with higher BMI were more likely to be teased. A prior study of G2 men (not just those who became fathers) did not support an association between their experiences being teased in childhood and adult BMI or obesity status (Kerr & Gini, 2017). Thus, findings are consistent with studies linking obesity to bullying and weight-related teasing (Griffiths et al, 2006; Jansen et al, 2014; Puhl et al, 2013) but do not support that intergenerational stability in peer victimization occurs via G3 BMI.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, apart from poor parenting or concurrent socioemotional risks, children with higher BMI were more likely to be teased. A prior study of G2 men (not just those who became fathers) did not support an association between their experiences being teased in childhood and adult BMI or obesity status (Kerr & Gini, 2017). Thus, findings are consistent with studies linking obesity to bullying and weight-related teasing (Griffiths et al, 2006; Jansen et al, 2014; Puhl et al, 2013) but do not support that intergenerational stability in peer victimization occurs via G3 BMI.…”
Section: Discussionmentioning
confidence: 91%
“…Findings from the National Heart, Lung, and Blood Institute Growth and Health Study ( N = 2,379) showed that girls who were called “too fat” by family members or peers had higher odds of obesity 9 years later, independent of initial weight status and adjusting for race and SES (Hunger & Tomiyama, 2014). While findings from Project EAT documented 15-year longitudinal associations between weight-teasing in adolescents and increased risk of obesity in adulthood for both males and females (Puhl et al, 2017), it may be that links between teasing/bullying and BMI are most pronounced for weight-specific rather than general (nonspecific) forms of victimization, as some evidence has found no associations between general teasing (not specific to weight) in adolescence with BMI over time for boys (Kerr & Gini, 2017; Wolke, Copeland, Angold, & Costello, 2013).…”
Section: Health Implications For Individuals With Heightened Vulnerab...mentioning
confidence: 99%
“…(Bautista, López y Franco, 2014;Bautista-Díaz et al, 2016;Chu et al, 2019;Contreras-Valdez, Hernández-Guzmán y Freyre, 2016;Durso et al, 2012;Gariepy, Nitka y Schmitz, 2010;Godoy, 2014;Reyes, Betancur y Samaniego, 2015;Salazar, Castillo, Pastor, Tejada-Tayabas y Palos, 2016;Wit et al, 2010). Finalmente, en la dimensión sociocultural, la estigmatización de que es objeto la obesidad y la discriminación que se ejerce sobre quien la presenta, pueden potenciar las consecuencias de las otras dos dimensiones (Heijens, Janssens y Streukens, 2011;Kerr y Gini, 2017;Puhl, 2009;Puhl y DePierre, 2012;Puhl y Heuer, 2010).…”
Section: Introductionunclassified